2021
DOI: 10.1016/s1473-3099(21)00069-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic stewardship interventions in primary care on antimicrobial resistance of Escherichia coli bacteraemia in England (2013–18): a quasi-experimental, ecological, data linkage study

Abstract: Background Antimicrobial resistance is a major global health concern, driven by overuse of antibiotics. We aimed to assess the effectiveness of a national antimicrobial stewardship intervention, the National Health Service (NHS) England Quality Premium implemented in 2015-16, on broad-spectrum antibiotic prescribing and Escherichia coli bacteraemia resistance to broad-spectrum antibiotics in England.Methods In this quasi-experimental, ecological, data linkage study, we used longitudinal data on bacteraemia for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…In contrast to the approach used in the latter and in other studies, e.g., as in Cuevas et al [ 16 ], we were able to quantify the impact on resistance of previous antibiotic use at an individual level, avoiding the risk of the so-called ecological fallacy. Some studies, also mostly ecological, showed persistent bacterial resistance despite reduced antibiotic use in E. coli and in other species [ 17 , 18 ], while other studies showed the opposite [ 10 , 19 , 20 ]. A possible explanation of these divergent findings is likely the fact that bacterial resistance is a complex phenomenon, with primary care prescribing being only one of its drivers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the approach used in the latter and in other studies, e.g., as in Cuevas et al [ 16 ], we were able to quantify the impact on resistance of previous antibiotic use at an individual level, avoiding the risk of the so-called ecological fallacy. Some studies, also mostly ecological, showed persistent bacterial resistance despite reduced antibiotic use in E. coli and in other species [ 17 , 18 ], while other studies showed the opposite [ 10 , 19 , 20 ]. A possible explanation of these divergent findings is likely the fact that bacterial resistance is a complex phenomenon, with primary care prescribing being only one of its drivers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 134 E. coli isolates collected from Hangzhou nosocomial bloodstream infections from 2013 to 2016, approximately 41.5% were identified as extended-spectrum blactamase (ESBL)-producing-positive by Jiang et al (2019). Even though medical institutions have imposed strict controls and rules on the use of antibiotics, publications suggest that the growing trend of drug resistance in E. coli continues (Aliabadi et al, 2021).…”
Section: Antibiotic Resistance Of Severalmentioning
confidence: 99%
“…(2019) . Even though medical institutions have imposed strict controls and rules on the use of antibiotics, publications suggest that the growing trend of drug resistance in E. coli continues ( Aliabadi et al., 2021 ).…”
Section: Antibiotic Resistance Of Several Prominent Toa Pathogensmentioning
confidence: 99%
“…( 21 ). As stewardship alone has been insufficient at slowing the spread of ESBL-producing E. coli ( 22 ), it is imperative to determine the drivers of its increasing colonization. Here, we developed a murine model in which mice were exposed to different antibiotics under various conditions to determine protective and antiprotective factors that altered pathogenic E. coli colonization persistence.…”
Section: Introductionmentioning
confidence: 99%